Structure and evolution-guided design of minimal RNA-guided nucleases - Petr Skopintsev; Isabel Esain-Garcia; Evan C. DeTurk; Peter H. Yoon; Zehan Zhou; Trevor Weiss; Maris Kamalu; Ajit Chamraj; Kenneth J. Loi; Conner J. Langeberg; Ron S. Boger; Hunter Nisonoff; et al. (Science, 2026)
The design of RNA-guided nucleases with properties not limited by evolution can expand programmable genome-editing capabilities. However, generating diverse multidomain proteins with robust enzymatic properties remains challenging. Here, we use a protein design strategy that couples a structure-guided inverse-folding model with evolution-informed residue constraints to generate active, divergent variants of TnpB, a minimal CRISPR-Cas12–like nuclease, termed SynTnpBs. High-throughput screening of artificial intelligence–generated variants yielded editors that retained or exceeded wild-type activity in bacterial, plant, and human cells. Cryo–electron microscopy–based structure determination of the most divergent variant revealed stabilizing contacts in the RNA–DNA interfaces across conformations, demonstrating the design potential of this approach. Together, these results establish a strategy for creating non-natural RNA-guided nucleases and conformationally active nucleic acid binders, enlarging the designable protein space.